RANCANGAN HETEROJUNCTION BIPOLAR TRANSISTOR SILIKON GERMANIUM (HBT’S SIGE) DENGAN PENDEKATAN POISSON EQUATION - Tossin Alamsyah; Endang Saepuddin (Jurnal Poli-Teknologi, 2011)
Ideally performance of Heterojunction Bipolar Transistor (SiGe HBT's) is the Threshold Frequency (ft) and Maximum Frequency (fmax) and high current gain. In order to get the performance can be used the physics approach that that is heavy doping on the emitter and narrow base width. This research conducted at the design of SiGe HBT's based on a model approach three (3)-dimensional hydrodynamic approach to the Poisson equation with electron transport. Simulation using the software Bipole3 with input parameters based on models developed by IBM's first generation. Results of analysis and discussion show that the design of SiGe HBT's provide the frequency threshold (FT) 56 GHz with a deviation of 7% of the worth of a model developed by IBM. Keywords: HBT’s SiGe, Poisson Equation. ABSTRAK Kinerja ideal dari Heterojunction Bipolar Transistor (HBT’s SiGe) adalah Threshold Frequency ( ft ) dan Maximum Frequency ( fmax ) serta Current Gain yang tinggi. Untuk mendapatkan unjuk kerja yang tersebut dapat digunakan pendekatan physic yaitu heavy doping pada emitter dan lebar basis dibuat sempit (narrow base width). Pada riset ini dilakukan rancangan HBT’s SiGe berdasarkan pendekatan model tiga(3) dimensi hydrodynamic dengan pendekatan Poisson equation electron transport. Simulasi menggunakan perangkat lunak Bipole3 dengan parameter masukan berdasarkan model yang dikembangkan oleh IBM generasi pertama Hasil analisa dan pembahasan menunjukkan bahwa hasil rancangan HBT’s SiGe menghasilkan frekuensi threshold (fT) 56 GHz dengan deviasi senilai 7% terhadap model yang dikembangkan oleh IBM. Kata kunci: HBT’s SiGe, Persamaan Poisson